The access to justice and deprivation of liberty in Argentina: Prison policies in light of the Brasilia Rules - Lombraña, Andrea (2021)
This article analyzes the National Penitentiary Policy Master Plan and the Strategic Plan of the Federal Penitentiary Service 2016/2020, and their merits and shortcomings in the Argentine prison context. Based on these instruments, and following the Brasilia Rules, it is proposed policies to prevent crime through four types of reforms: a) normative, regarding the progressiveness of the sentence, the regulation of the work activity of persons deprived of liberty in the penitentiary situation, the education and training of personnel, as well as the procedure regarding their entry, promotion, and discharge, in addition to the assimilation of the gender perspective in institutional policy; b) infrastructural, that is, the construction of prisons and their organization to reduce overcrowding; c) resocialization of inmates in penitentiary establishments; and finally, d) integration for the strengthening of relations between civil society organizations, institutional control and scientific and technical agencies such as the Conicet.